F23 Validity, reliability, ability to detect change and meaningful within-patient change of the CUHDRS. (September 2018) - Trundell, Dylan; Palermo, Giuseppe; Schobel, Scott; Long, Jeffrey D; Leavitt, Blair R; Tabrizi, Sarah J
Abstract : Background: The composite Unified Huntington's Disease Ratings Scale (cUHDRS) is a combined score of measures of motor function (TMS), cognition (SDMT and SWR) and overall functional capacity (TFC). The cUHDRS was developed to assess multi-domain clinical progression in Huntington's disease (HD), and was shown to be a sensitive, reliable, and valid. To support its use in clinical studies, further evidence is required. This includes estimates of clinically meaningful change of the cUHDRS and its individual measures. Aims: To assess the reliability, validity and ability to detect change of the cUHDRS and to estimate minimal clinically meaningful within-patient cUHDRS change. Methods: Data from an early manifest HD population (TFC≥5) from two multi-national registries (ENROLL-HD and REGISTRY) were used. Test-retest reliability was assessed by calculating the intraclass correlation coefficient (ICC) in a subset of patients with no change in Clinical Global Impression of Severity (CGI-S) score. Convergent validity was assessed by Spearman rank order correlations. Known-groups validity was assessed by analysis of covariance (ANCOVA) between groups defined by CGI-S. Ability to detect change was assessed by ANCOVA comparing groups based on CGI-S score change. Regression analyses were conducted to estimate meaningful change, using CGI-S and Independence Scale (IS) as anchors. Results: Strong evidence of test-retest reliability, known-groups validity and ability to detect change was demonstrated. Convergent validity was supported by stronger correlations with measures that are more similar. Meaningful within-patient change was estimated. Conclusions: cUHDRS is valid, reliable and able to detect change in patients with early manifest HD. Analyses anchored against CGI-S and IS support that a decline on the cUHDRS is clinically meaningful. Acknowledgements: Funded by F. Hoffmann-La Roche.